Experiencia del duelo de las familias con un integrante fallecido por causa del Covid-19 en el municipio de Maicao - Villamizar Arellano, Natalie Liseth; Solano Pérez, Alex Mauricio (Universidad Antonio Nariño, 2023)
Taking into account that the pandemic was a problem that affected all people worldwide; in which families from different economic backgrounds, socio-cultural contexts, etc. were affected; That is why it is understood that Covid-19 is an incident that had repercussions on the quality of life of people and that affected the mourning process of people who found themselves immersed in the death of relatives by Covid-19.